Modified crosslinked polystyrene plastic scintillator and preparation method thereof

The modified cross-linked polystyrene plastic scintillator addresses brittleness and efficiency issues by incorporating a cross-linking agent and enhancer, achieving enhanced mechanical strength and fluorescence, suitable for neutron and radionuclide detection.

CN119161539APending Publication Date: 2024-12-20SHENZHEN KERUIWO TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411494552.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Existing plastic scintillators face issues such as brittle cracking, insufficient mechanical strength, low fluorescence quantum efficiency, and high organic waste generation, limiting their effectiveness in neutron and radionuclide detection.

Method used

A modified cross-linked polystyrene plastic scintillator is prepared using styrene as a reaction monomer, combined with a cross-linking agent, initiator, and enhancer, and luminescent substances, with controlled polymerization conditions to enhance mechanical strength and fluorescence efficiency.

Benefits of technology

The solution results in a scintillator with improved mechanical strength, temperature resistance, and fluorescence characteristics, suitable for commercial production and applications in neutron detection and radionuclide analysis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161539A_ABST
    Figure CN119161539A_ABST
Patent Text Reader

Abstract

The invention relates to a plastic scintillator, in particular to a modified crosslinked polystyrene plastic scintillator and a preparation method thereof. The plastic scintillator comprises a reaction monomer, a cross-linking agent, an initiator, a reinforcing agent and a luminescent substance, a reaction monomer is styrene, and the preparation method comprises the following steps: step 1, obtaining a polystyrene solution by using a method of pre-polymerizing styrene or dissolving polystyrene powder in styrene; according to the technical scheme, styrene is adopted as a reaction monomer matrix, the cross-linking agent and the reinforcing agent are introduced, and the three components have a synergistic effect to generate a copolymer, so that intermolecular linkage is tighter; the prepared plastic scintillator not only greatly shortens the polymerization reaction time, but also has higher mechanical strength, excellent high temperature resistance and excellent fluorescence characteristic. The method is ingenious in design, simple and convenient to implement and remarkable in effect, and is expected to be widely applied to commercial production of plastic scintillators.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a plastic scintillator, and in particular to a modified cross-linked polystyrene plastic scintillator and a preparation method thereof. Background Art

[0002] With the vigorous development of my country's nuclear technology, radioactive materials have been widely used in many fields such as national defense, medical treatment, industry, agriculture and scientific research. In the field of radiation safety monitoring, the importance of radiation detection is self-evident. Since neutrons have strong penetrating power, they pose a potential hazard to the human body, and neutrons are uncharged and difficult to detect directly. Therefore, detection is usually carried out through secondary particles generated by the interaction between neutrons and specific substances.

[0003] Scintillators are commonly used light conversion devices for diagnosing rays or particles produced by nuclear reactions, and they play a vital role in the study of high-energy particles. Scintillators have corresponding performance requirements according to different application needs. Neutron detection can be divided into nuclear recoil method, nuclear reaction method, nuclear fission method, etc. according to the interaction between neutrons and matter. The principle of the nuclear recoil method is that neutrons interact with matter through elastic scattering to produce recoil protons. Since the elastic scattering cross-sections of elements such as C, H, and O are large, plastic scintillators have become one of the key detectors for detecting neutrons.

[0004] The alpha and beta emissions of radionuclides have a short range, especially the alpha nuclide, which has a range of only a few centimeters. Therefore, to detect such nuclides, the detector material needs to be in close contact with the radionuclides. Currently, liquid scintillation spectrometry is the most commonly used method for measuring radionuclides, but it has limitations in continuous measurement and high-salinity measurement. In addition, the use of liquid scintillation spectrometers also produces a large amount of organic radioactive waste liquid, and the treatment of these waste liquids is extremely challenging. To solve this problem, the use of plastic scintillators is a more effective strategy.

[0005] Reports show that my country has mastered the technology of preparing organic plastic scintillators using polyvinyltoluene as the matrix material, but the content of luminescent substances in such plastic scintillators is only 30% at most. The higher the content of luminescent substances, the better the n-γ resolution performance of the plastic scintillator. In the preparation of plastic scintillators, polystyrene (PS) and polyvinyltoluene (PVT) are commonly used matrices. However, plastic scintillators using only these pure matrices have problems such as brittle cracking, insufficient mechanical strength, and low fluorescence quantum efficiency. Summary of the invention

[0006] The purpose of the present application is to propose a modified cross-linked polystyrene plastic scintillator and a preparation method thereof which have significantly improved mechanical strength, temperature resistance, preparation time and luminous efficiency.

[0007] One of the technical solutions of the present application is achieved as follows: a method for preparing a modified cross-linked polystyrene plastic scintillator, which includes the plastic scintillator comprising a reaction monomer, a cross-linking agent, an initiator, an enhancer and a luminescent substance; the reaction monomer is styrene, and is prepared according to the following steps: The first step is to obtain a polystyrene solution by prepolymerizing styrene or dissolving polystyrene powder in styrene, and then mix the primary luminescent material and the secondary luminescent material with the polystyrene solution and fully disperse them to obtain a precursor solution A; The second step is to fully stir and mix the crosslinking agent, initiator and enhancer with the precursor solution A obtained in the first step to obtain a mixed solution B; Step 3: Pour the mixed solution B obtained in step 2 into a mold with a flat bottom, and then freeze the entire mold to solidify; The fourth step is to transfer the product of the third step to a vacuum oven for polymerization reaction.

[0008] Furthermore, the crosslinking agent is one or more combinations of divinylbenzene, ethylene glycol dimethacrylate, and pentaerythritol tetraacrylate; the crosslinking agent is divinylbenzene, and its mass accounts for 1% to 5% of the reaction monomers; the crosslinking agent is ethylene glycol dimethacrylate, and its mass accounts for 5% to 10% of the reaction monomers; the crosslinking agent is pentaerythritol tetraacrylate, and its mass accounts for 2% to 10% of the reaction monomers.

[0009] Furthermore, the initiator is one or more combinations of azobisisobutyronitrile, azobisisoheptylnitrile, dibenzoyl peroxide, potassium persulfate, cumene hydroperoxide, diisopropyl peroxydicarbonate, and tert-butyl perbenzoate, and its mass accounts for 0.01% to 2% of the reaction monomers; or / and, the enhancer is one or more of acrylonitrile, methyl methacrylate, and butyl acrylate, and its mass accounts for 10% to 25% of the reaction monomers.

[0010] Furthermore, the luminescent material includes a main luminescent material and a secondary luminescent material. The main luminescent material is biphenyl or 2,5-diphenyloxazole, and its mass accounts for 5% to 30% of the reaction monomer; the secondary luminescent material is one of 9,10-diphenylanthracene or 1,4-bis(5-phenyloxazole)benzene, and its mass accounts for 0.01% to 0.6% of the reaction monomer.

[0011] Furthermore, the viscosity of the mixed solution B obtained in the second step is between 500 Pa·s and 3000 mPa·s.

[0012] Furthermore, in the third step, the entire mold is placed in a liquid nitrogen freezer to solidify; the freezer temperature is maintained at -35°C to -70°C, and the freezing time is 1 hour to 5 hours.

[0013] Furthermore, in the fourth step, the vacuum oven needs to be connected to nitrogen or argon circulation as a protective gas; the polymerization reaction process: first at 40°C to 45°C, keep warm for 24 to 36 hours; then increase the temperature to 50°C to 60°C at a rate of 1°C / h to 3°C / h, and keep warm for 4h to 60h; then cool down to 45°C to 50°C at a rate of 3°C to 5°C / h, and keep warm for 12h to 24h; then increase the temperature to 100°C to 110°C at a rate of 5°C / h to 10°C / h, and keep warm for 24h to 48h; then cool down to 40°C to 45°C at a rate of 3°C / h to 5°C / h, and keep warm for 12h to 24h; after the insulation is completed, naturally cool to room temperature.

[0014] The second technical solution of the present application is achieved as follows: a modified cross-linked polystyrene plastic scintillator is prepared by a method for preparing a modified cross-linked polystyrene plastic scintillator.

[0015] Due to the implementation of the above technical solution, this application adopts styrene as the reaction monomer matrix, introduces a cross-linking agent and a reinforcing agent, and the three work together to generate a copolymer, making the molecular connection tighter; the plastic scintillator prepared in this way not only greatly shortens the polymerization reaction time, but also has high mechanical strength, excellent high temperature resistance and excellent fluorescence characteristics. On the basis of ensuring the mechanical properties of the plastic scintillator, the fluorescence intensity is also guaranteed, and the optical properties of the scintillator are improved. The present invention is exquisitely designed, simple to implement, and has remarkable results, and is expected to be widely used in the commercial production of plastic scintillators. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] The specific structure of this application is given by the following drawings and embodiments: Figure 1 is a schematic diagram of light transmittance curves of Example 1, Example 2, and Example 3 of the present application; Figure 2 It is a schematic diagram of the thermogravimetric analysis results of Examples 1, 2 and 3 of the present application; Figure 3 This is a photo of Example 4 of the present application; Figure 4 This is a photo of Example 4 of the present application. DETAILED DESCRIPTION

[0017] The present application is not limited by the following embodiments, and the specific implementation method can be determined according to the technical solution of the present application and actual conditions.

[0018] Embodiment 1, as Figure 1 As shown, a modified cross-linked polystyrene plastic scintillator and a preparation method thereof include: the plastic scintillator includes a reaction monomer, a cross-linking agent, an initiator, an enhancer and a luminescent substance; the reaction monomer is styrene, and is prepared according to the following steps: The first step is to obtain a polystyrene solution by prepolymerizing styrene or dissolving polystyrene powder in styrene, and then mix the primary luminescent material and the secondary luminescent material with the polystyrene solution and fully disperse them to obtain a precursor solution A; The second step is to fully stir and mix the crosslinking agent, initiator and enhancer with the precursor solution A obtained in the first step to obtain a mixed solution B; Step 3: Pour the mixed solution B obtained in step 2 into a mold with a flat bottom, and then freeze the entire mold to solidify; The fourth step is to transfer the product of the third step to a vacuum oven for polymerization reaction.

[0019] Polystyrene (PS) has become the most commonly used scintillator matrix material due to its low cost and high detection efficiency.

[0020] The plastic scintillator produced in this application is easy to use, has low preparation cost and strong plasticity, and has been widely used in the detection field. Compared with gas scintillator detectors and liquid scintillator detectors, plastic scintillator has a higher cost performance and is easy to make into various sizes and shapes. In addition, it has low toxicity and high mechanical strength, and can work normally in complex and harsh environments. The cost of raw materials is relatively high. 3 The He content is low, the preparation process is relatively simple, the response speed is fast, and it is suitable for high-speed acquisition systems at high count rates. Plastic scintillator neutron detection has shown excellent performance in many fields, such as aerospace, nuclear energy, and nuclear safety.

[0021] Plastic scintillators can be used to detect α, β, γ, fast neutrons, protons and cosmic rays, etc. They have the characteristics of no deliquesce, high stability, radiation resistance and short scintillation decay time.

[0022] like Figure 3 , Figure 4 As shown, the present application uses styrene as a reaction monomer matrix, and by introducing a cross-linking agent and a reinforcing agent, the three work together to generate a copolymer, making the molecular connection tighter. The plastic scintillator prepared in this way not only greatly shortens the polymerization reaction time, but also has high mechanical strength, excellent high temperature resistance and excellent fluorescence characteristics. On the basis of ensuring the mechanical properties of the plastic scintillator, the fluorescence intensity is also guaranteed, and the optical properties of the scintillator are improved. The present invention is exquisitely designed, simple to implement, and has significant results. It is expected to be widely used in the commercial production of plastic scintillators. Compared with pure matrix plastic scintillators, the plastic scintillator produced by this application has significantly improved mechanical strength, temperature resistance, preparation time, and luminous efficiency, thereby further expanding its scope of application. The plastic scintillator prepared by this method can be widely used in nuclear industry monitoring, high energy physics research, and nuclear safety.

[0023] The crosslinking agent is one or more combinations of divinylbenzene, ethylene glycol dimethacrylate, and pentaerythritol tetraacrylate; the crosslinking agent is divinylbenzene, and its mass accounts for 1% to 5% of the reaction monomers; the crosslinking agent is ethylene glycol dimethacrylate, and its mass accounts for 5% to 10% of the reaction monomers; the crosslinking agent is pentaerythritol tetraacrylate, and its mass accounts for 2% to 10% of the reaction monomers.

[0024] The initiator is one or more of azobisisobutyronitrile, azobisisoheptylnitrile, dibenzoyl peroxide, potassium persulfate, cumene hydroperoxide, diisopropyl peroxydicarbonate, and tert-butyl perbenzoate, and the mass of the initiator is 0.01% to 2% of the reaction monomers; or / and the enhancer is one or more of acrylonitrile, methyl methacrylate, and butyl acrylate, and the mass of the initiator is 10% to 25% of the reaction monomers.

[0025] The luminescent material includes a primary luminescent material and a secondary luminescent material. The primary luminescent material is biphenyl or 2,5-diphenyloxazole, and its mass accounts for 5% to 30% of the reaction monomer; the secondary luminescent material is one of 9,10-diphenylanthracene or 1,4-bis(5-phenyloxazole)benzene, and its mass accounts for 0.01% to 0.6% of the reaction monomer.

[0026] 2,5-diphenyloxazole (PPO for short), 9,10-diphenylanthracene (DPA for short) or 1,4-bis(5-phenyloxazole)benzene (POPOP for short); the secondary luminescent substance is also called wavelength shifter.

[0027] The main luminescent material accounts for a large proportion of the mass because high concentration of luminescent material doping can increase the probability of triplet-triplet collisions, transferring the energy captured from the matrix to the molecules of the main luminescent material, and then to the molecules of the secondary luminescent material (wave shifter). However, doping with high concentrations of the main fluorescent dye will lead to self-absorption effects and weaken the fluorescence emission intensity. Therefore, adding a low doping concentration of secondary luminescent materials can improve the transparency of the scintillator and realize the energy transfer of triplet molecules in the main fluorescent dye, thereby reducing the self-absorption effect.

[0028] The viscosity of the mixed solution B obtained in the second step is between 500 Pa·s and 3000 mPa·s.

[0029] In the third step, the entire mold is placed in liquid nitrogen freezing liquid to solidify; the freezing liquid temperature is maintained at -35°C to -70°C, and the freezing time is 1 hour to 5 hours.

[0030] In the fourth step, the vacuum oven needs to be connected to nitrogen or argon circulation as a protective gas; polymerization reaction process: first at 40 ℃ to 45 ℃ temperature, keep warm for 24 to 36 hours; then increase the temperature to 50 ℃ to 60 ℃ at a rate of 1 ℃ / h to 3 ℃ / h, keep warm for 4 hours to 60 hours; then cool down to 45 ℃ to 50 ℃ at a rate of 3 ℃ to 5 ℃ / h, and keep warm for 12 hours to 24 hours; then increase the temperature to 100 ℃ to 110 ℃ at a rate of 5 ℃ / h to 10 ℃ / h, and keep warm for 24 hours to 48 hours; then cool down to 40 ℃ to 45 ℃ at a rate of 3 ℃ / h to 5 ℃ / h, and keep warm for 12 hours to 24 hours; after the insulation is completed, naturally cool to room temperature.

[0031] If the starting temperature of the polymerization reaction is too high or the heating rate is too fast, bubbles may be generated in the mixed liquid, which are difficult to eliminate and thus affect the uniformity of the plastic scintillator. Secondly, if the starting temperature of the polymerization reaction is too low or the heating rate is too slow, the polymerization reaction time will be prolonged, while the hardness of the plastic scintillator after polymerization will be reduced and the polymerization time will be increased. Finally, during the cooling process, proper insulation is required to ensure that the polymerization reaction proceeds fully, thereby obtaining excellent mechanical properties.

[0032] like Figure 3 , Figure 4 By precisely controlling the mass ratio of each substance and rationally adjusting the heating steps, the polymerization reaction process can be ensured to proceed comprehensively and stably, so that all substances can be fully reacted. In addition, during the heating and cooling process, a gradient heating and cooling strategy is adopted to prevent the formed plastic scintillator from cracking due to drastic temperature changes, thereby shortening the polymerization time to 6-7 days, and finally obtaining a plastic scintillator with high temperature tolerance, high hardness, high transparency and high fluorescence emission intensity.

[0033] Example 1: 200g of styrene (St), 10g of the main fluorescent dye 2,5-diphenyloxazole (PPO), and 0.2g of the wavelength shift agent 9,10-diphenylanthracene (DPA) are mixed and stirred uniformly according to mass percentage to form a precursor solution A; then 8g of divinylbenzene (DVB), 3g of azobisisobutyronitrile (AIBN), and 30g of acrylonitrile (AN) are mixed and stirred with the uniformly stirred A. In order to facilitate complete dissolution and dispersion, it can be placed in a warm water bath at 35°C; the uniformly dispersed solution is slowly added to the mold, and then the entire mold is placed in a liquid nitrogen freezer to solidify, the freezer temperature is maintained at -50°C to -55°C, the freezing time is 1.5 hours, and then transferred to a vacuum oven. The oven needs to be connected to nitrogen or argon circulation as a protective gas to add liquid nitrogen to solidify the liquid, and then the temperature is increased and solidified under vacuum conditions. The treated mixed solution was heated by gradient temperature increase, and the polymerization reaction process was as follows: first, at 40-42°C, the temperature was kept for 24 hours; then, the temperature was increased to 50-60°C at a rate of 3°C / h, and the temperature was kept for 48 hours; then, the temperature was decreased to 45°C at a rate of 5°C / h, and the temperature was kept for 12 hours; then, the temperature was increased to 105°C at a rate of 6°C / h, and the temperature was kept for 48 hours; then, the temperature was decreased to 45°C at a rate of 3°C / h, and the temperature was kept for 12 hours; after the temperature was kept, the mixture was naturally cooled to room temperature. The organic plastic scintillator blank was obtained. The organic plastic scintillator blank was mechanically cut and polished to obtain an organic plastic scintillator sample with excellent mechanical strength and fluorescence effect.

[0034] The test results show that the density of the plastic scintillator is 1.045g / cm3, the refractive index is 1.59, the softening temperature is 91℃, and the scintillation decay time is 2.4ns. In the spectrum test, the fluorescence peak of PPO is 365nm, and the fluorescence emission peak of DPA is 412nm and 432nm. There are no bubbles inside the plastic scintillator, the transparency is high, and the light transmittance is 91%. The hardness of the plastic scintillator is tested by pressing the surface of the plastic scintillator with a metal probe and reading the depth of the elastic deformation of the probe. The Shore D hardness of the material is 81. The value of the Shore D hardness indicates the hardness of the material.

[0035] Example 2: 150g of general-purpose polystyrene (GPPS) particles were processed into powder using a pulverizer. The temperature during the pulverization process was controlled at room temperature and the environment was kept dry (humidity <40%). The pulverized powder was then mixed with 50g of styrene to test that the polystyrene powder was completely dissolved in the styrene. Then, 200g of the polystyrene solution, 12g of the primary fluorescent dye 2,5-diphenyloxazole (PPO), and 0.15g of the wavelength shift agent 9,10-diphenylanthracene (DPA) were mixed according to mass percentage and stirred thoroughly to form a precursor solution A. Then, 8 1. g divinylbenzene (DVB), 3 g dibenzoyl peroxide (BPO), 20 g methyl methacrylate (MMA) are mixed with the stirred A. In order to facilitate complete dissolution and dispersion, it can be placed in a warm water bath at 35°C; the evenly dispersed solution is slowly added to the mold, and then the entire mold is placed in liquid nitrogen freezing liquid to solidify, and the freezing liquid temperature is maintained at -50°C to -55°C. The freezing time is 1.5 hours, and then it is transferred to a vacuum oven. The oven needs to be connected to nitrogen or argon circulation as a protective gas. Liquid nitrogen is added to solidify the liquid, and then the temperature is increased and solidified under vacuum conditions. The treated mixed solution was heated by gradient temperature increase, and the polymerization reaction process was as follows: first, at 40°C to 42°C, the temperature was kept for 24 hours; then, the temperature was increased to 50°C to 60°C at a rate of 3°C / h, and the temperature was kept for 48 hours; then, the temperature was decreased to 45°C at a rate of 5°C / h, and the temperature was kept for 12 hours; then, the temperature was increased to 105°C at a rate of 6°C / h, and the temperature was kept for 48 hours; then, the temperature was decreased to 45°C at a rate of 3°C / h, and the temperature was kept for 12 hours; after the temperature was kept, the mixture was naturally cooled to room temperature. The organic plastic scintillator blank was obtained. The organic plastic scintillator blank was mechanically cut and polished to obtain an organic plastic scintillator sample with excellent mechanical strength and fluorescence effect.

[0036] The test results show that the density of the plastic scintillator is 1.047g / cm3, the refractive index is 1.58, the softening temperature is 97℃, and the scintillation decay time is 2.4ns. In the spectrum test, the fluorescence peak of PPO is 365nm, and the fluorescence emission peak of DPA is 412nm and 432nm. There are no bubbles inside the plastic scintillator, and the transparency is high, with a light transmittance of 90.8%. The hardness of the plastic scintillator is tested by applying pressure to the surface of the plastic scintillator with a metal probe and reading the depth of the elastic deformation of the probe. The Shore D hardness of the material is 79. The Shore D hardness value indicates the hardness of the material.

[0037] Example 3: 150g of general-purpose polystyrene (GPPS) particles were processed into powder using a pulverizer. The temperature during the pulverization process was controlled at room temperature and the environment was kept dry (humidity <40%). The pulverized powder was then mixed with 50g of styrene to test that the polystyrene powder was completely dissolved in the styrene. Then, 200g of the polystyrene solution, 12g of the main fluorescent dye 2,5-diphenyloxazole (PPO), and 0.15g of the wavelength shift agent 1,4-bis(5-phenyloxazole)benzene (POPOP) were mixed according to mass percentage and stirred thoroughly to form a precursor solution A. Mix 6g of pentaerythritol tetraacrylate (PETA), 3g of azobisisobutyronitrile (AIBN), and 24g of butyl acrylate (BA) with the stirred A. In order to facilitate complete dissolution and dispersion, it can be placed in a warm water bath at 35°C; slowly add the evenly dispersed solution to the mold, and then place the entire mold in liquid nitrogen freezing liquid to solidify, maintain the freezing liquid temperature at -50°C to -55°C, and freeze for 1.5 hours. Then transfer it to a vacuum oven. The oven needs to be connected to nitrogen or argon circulation as a protective gas. Liquid nitrogen is added to solidify the liquid, and then the temperature is increased and solidified under vacuum conditions. The treated mixed solution was heated by gradient temperature increase, and the polymerization reaction process was as follows: first, at 40°C to 42°C, the temperature was kept for 24 hours; then, the temperature was increased to 50°C to 60°C at a rate of 3°C / h, and the temperature was kept for 48 hours; then, the temperature was decreased to 45°C at a rate of 5°C / h, and the temperature was kept for 12 hours; then, the temperature was increased to 105°C at a rate of 6°C / h, and the temperature was kept for 48 hours; then, the temperature was decreased to 45°C at a rate of 3°C / h, and the temperature was kept for 12 hours; after the temperature was kept, the mixture was naturally cooled to room temperature. The organic plastic scintillator blank was obtained. The organic plastic scintillator blank was mechanically cut and polished to obtain an organic plastic scintillator sample with excellent mechanical strength and fluorescence effect.

[0038] The test results show that the density of the plastic scintillator is 1.051g / cm3, the refractive index is 1.59, the softening temperature is 102℃, and the scintillation decay time is 2.4ns. In the spectrum test, the fluorescence peak of PPO is 365nm, and the fluorescence emission peak of DPA is 412nm and 432nm. There are no bubbles inside the plastic scintillator, and the transparency is high, with a light transmittance of 91.4%. The hardness of the plastic scintillator is tested by applying pressure to the surface of the plastic scintillator with a metal probe and reading the depth of the elastic deformation of the probe. The Shore D hardness of the material is 84. The value of the Shore D hardness indicates the hardness of the material.

[0039] pass Figure 1 Analysis shows that for the 200nm to 400nm band, the scintillator has a strong absorption effect, with a transmittance of less than 5%. In the band greater than 410nm, the transmittance is around 90%. It can be seen that it has good transparency, reduces the self-absorption of the plastic scintillator, and reduces losses during energy transfer.

[0040] pass Figure 2 Analysis shows that when the weight loss is 5%, the initial weight loss of Example 1 is the largest, indicating that the addition of DVB cross-linking agent improves the thermal stability of the plastic scintillator and enables the plastic scintillator to maintain good stability at higher temperatures. The effects of adding other concentrations of cross-linking agent in Examples 2 and 3 are similar but not as good as Example 1.

[0041] Example 4: A modified cross-linked polystyrene plastic scintillator prepared according to a modified cross-linked polystyrene plastic scintillator preparation method, the diameter of which can reach 70 mm and the thickness of which ranges from 10 mm to 100 mm.

[0042] In this document, “upper”, “lower”, “front”, “back”, “left”, “right”, etc. are only used to indicate the relative position relationship between related parts, rather than to limit the absolute positions of these related parts.

[0043] The above technical features constitute the embodiments of the present application, which have strong adaptability and implementation effect. Non-essential technical features can be added or reduced according to actual needs to meet the needs of different situations.

Claims

1. A method for preparing a modified cross-linked polystyrene plastic scintillator, characterized in that: The plastic scintillator comprises a reaction monomer, a cross-linking agent, an initiator, an enhancer and a luminescent substance; the reaction monomer is styrene, and is prepared according to the following steps: The first step is to obtain a polystyrene solution by prepolymerizing styrene or dissolving polystyrene powder in styrene, and then mix the primary luminescent material and the secondary luminescent material with the polystyrene solution and fully disperse them to obtain a precursor solution A; The second step is to fully stir and mix the crosslinking agent, initiator and enhancer with the precursor solution A obtained in the first step to obtain a mixed solution B; Step 3: Pour the mixed solution B obtained in step 2 into a mold with a flat bottom, and then freeze the entire mold to solidify; The fourth step is to transfer the product of the third step to a vacuum oven for polymerization reaction.

2. The method for preparing a modified cross-linked polystyrene plastic scintillator according to claim 1, characterized in that: The crosslinking agent is one or more combinations of divinylbenzene, ethylene glycol dimethacrylate, and pentaerythritol tetraacrylate; the crosslinking agent is divinylbenzene, and its mass accounts for 1% to 5% of the reaction monomers; the crosslinking agent is ethylene glycol dimethacrylate, and its mass accounts for 5% to 10% of the reaction monomers; the crosslinking agent is pentaerythritol tetraacrylate, and its mass accounts for 2% to 10% of the reaction monomers.

3. The method for preparing a modified cross-linked polystyrene plastic scintillator according to claim 2, characterized in that: The initiator is one or more of azobisisobutyronitrile, azobisisoheptylnitrile, dibenzoyl peroxide, potassium persulfate, cumene hydroperoxide, diisopropyl peroxydicarbonate, and tert-butyl perbenzoate, and the mass of the initiator is 0.01% to 2% of the reaction monomers; or / and the enhancer is one or more of acrylonitrile, methyl methacrylate, and butyl acrylate, and the mass of the initiator is 10% to 25% of the reaction monomers.

4. The method for preparing a modified cross-linked polystyrene plastic scintillator according to claim 3, characterized in that: The luminescent material includes a primary luminescent material and a secondary luminescent material. The primary luminescent material is biphenyl or 2,5-diphenyloxazole, and its mass accounts for 5% to 30% of the reaction monomer; the secondary luminescent material is one of 9,10-diphenylanthracene or 1,4-bis(5-phenyloxazole)benzene, and its mass accounts for 0.01% to 0.6% of the reaction monomer.

5. A method for preparing a modified cross-linked polystyrene plastic scintillator according to claim 1, 2, 3 or 4, characterized in that: The viscosity of the mixed solution B obtained in the second step is between 500 Pa·s and 3000 mPa·s.

6. A method for preparing a modified cross-linked polystyrene plastic scintillator according to claim 1, 2, 3 or 4, characterized in that: In the third step, the entire mold is placed in liquid nitrogen freezing liquid to solidify; the freezing liquid temperature is maintained at -35°C to -70°C, and the freezing time is 1 hour to 5 hours.

7. The method for preparing a modified cross-linked polystyrene plastic scintillator according to claim 5, characterized in that: In the third step, the entire mold is placed in liquid nitrogen freezing liquid to solidify; the freezing liquid temperature is maintained at -35°C to -70°C, and the freezing time is 1 hour to 5 hours.

8. A method for preparing a modified cross-linked polystyrene plastic scintillator according to claim 1, 2, 3 or 4, characterized in that: In the fourth step, the vacuum oven needs to be connected to nitrogen or argon circulation as a protective gas; polymerization reaction process: first at 40 ℃ to 45 ℃ temperature, keep warm for 24 to 36 hours; then increase the temperature to 50 ℃ to 60 ℃ at a rate of 1 ℃ / h to 3 ℃ / h, keep warm for 4 hours to 60 hours; then cool down to 45 ℃ to 50 ℃ at a rate of 3 ℃ to 5 ℃ / h, and keep warm for 12 hours to 24 hours; then increase the temperature to 100 ℃ to 110 ℃ at a rate of 5 ℃ / h to 10 ℃ / h, and keep warm for 24 hours to 48 hours; then cool down to 40 ℃ to 45 ℃ at a rate of 3 ℃ / h to 5 ℃ / h, and keep warm for 12 hours to 24 hours; after the insulation is completed, naturally cool to room temperature.

9. The method for preparing a modified cross-linked polystyrene plastic scintillator according to claim 7, characterized in that: In the fourth step, the vacuum oven needs to be connected to nitrogen or argon circulation as a protective gas; polymerization reaction process: first at 40 ℃ to 45 ℃ temperature, keep warm for 24 to 36 hours; then increase the temperature to 50 ℃ to 60 ℃ at a rate of 1 ℃ / h to 3 ℃ / h, keep warm for 4 hours to 60 hours; then cool down to 45 ℃ to 50 ℃ at a rate of 3 ℃ to 5 ℃ / h, and keep warm for 12 hours to 24 hours; then increase the temperature to 100 ℃ to 110 ℃ at a rate of 5 ℃ / h to 10 ℃ / h, and keep warm for 24 hours to 48 hours; then cool down to 40 ℃ to 45 ℃ at a rate of 3 ℃ / h to 5 ℃ / h, and keep warm for 12 hours to 24 hours; after the insulation is completed, naturally cool to room temperature. 10 . A modified cross-linked polystyrene plastic scintillator prepared according to the method for preparing a modified cross-linked polystyrene plastic scintillator according to any one of claims 1 to 9 .